Lembar Kerja Peserta Didik Berbasis Konstruktivis untuk Kemampuan Berpikir Kritis Peserta Didik Sekolah Dasar - Irfan Septian; Syahril Syahril; Yalvema Miaz; Yeni Erita (Universitas Negeri Padang, 2022)
This study aims to produce student worksheets (LKPD) using a constructivist approach that is valid, practical, and effective in thematic learning in fifth-grade elementary school. The research method used is Research and Development (R and D) with a 4D model consisting of four phases, namely defining, designing plans, developing, and disseminating LKPD. Data were collected using document analysis, observation, interviews, field notes, tests, and questionnaires. The results showed that LKPD related to aspects of content, approach, format, language, and presentation were in the very valid category with an average percentage of 84.67%. The results of observations, questionnaires, and interviews showed the very practical category with a percentage of 86.43%. The critical thinking skills of students were developed and improved with a percentage of 79.37% developed effectively. Students can understand, find, analyze, collaborate, try and solve problems related to everyday life in thematic learning.